Analytical Method Development and Validation for Simultaneous Estimation of Antiviral Drug in Bulk and Pharmaceutical Dosage Form by RP-HPLC - Vaibhav S. Adhao,; Nikhil B. Kotgale,; Ashish M. Rathi,; Jaya P. Ambhore, (Asian Journal of Pharmaceutical Research and Development, 2024)
A new simple, specific, accurate, and precise RP-HPLC method has been developed and validated for the simultaneous estimation of Nirmatrelvir and Ritonavir in bulk and pharmaceutical dosage forms. The chromatographic separation was achieved using a Thermo fisher Scientific C18(250mm x 4.6mm, 5µm) with a mobile phase comprising a mixture of acetonitrile and phosphate buffer (70:30,), pumped at a flow rate of 1.0 mL/min and runtime of 6 minutes. The detection was performed at a wavelength of 221 nm. Under optimized chromatographic conditions, Nirmatrelvir and Ritonavir were eluted with retention times of 2.8 min and 3.9 min, respectively. Validation parameters were in compliance with ICH guidelines. These methods can be utilized for the routine determination of Nirmatrelvir and Ritonavir in bulk drug and formulation.